Fabrication, characterization and comparison of DSSC using anatase TiO 2 synthesized by various methods - Umale, Sanjivani V.; Tambat, Sneha N.; Vediappan, Sudhakar; Sontakke, Sharad M.; Krishnamoorthy, Kothandam (Advanced Powder Technology, 2017)
In this study, anatase TiO2 nanoparticles were synthesized by three techniques, namely, sol-gel, acid-base co-catalyst and room temperature colloidal methods. The synthesized materials were characterized by X-ray diffraction, scanning electron microscopy, pore diameter, pore volume and surface area. The dye-sensitized solar cells were fabricated using the synthesized materials and characterized for incident photon to current conversion efficiency, photocurrent density to photo voltage measurement and electrochemical impedance analysis. Among the studied materials, TiO2 synthesized by sol-gel method displayed highest photon to current conversion of 76.8% and a maximum solar cell efficiency of 7.85% with Jsc of 14.75mA/cm², Voc of 0.76V and FF of 0.7. This is the first study to report a high power conversion efficiency of DSSC using a sol-gel synthesized titania and its comparison with other two synthesized materials. The high power conversion efficiency of the solar cell using TiO2 synthesized by sol-gel method is attributed to its characteristic properties such high surface area, larger pore diameter and larger pore volume and highest dye loading capacity.

Improved efficiency of DSSC using combustion synthesized TiO2 - Umale, Sanjivani; Sudhakar, V.; Sontakke, Sharad M.; Krishnamoorthy, K.; Pandit, Aniruddha B. (Materials Research Bulletin, 2019)
Combustion synthesis method is an economic, one step and an effective method for the synthesis of nanomaterials. In this work, titanium dioxide nanoparticles were synthesized by combustion method. The synthesized material was characterized by XRD, SEM and BET. Dye sensitized solar cell was fabricated using the synthesized material and its performance was compared with the solar cell fabricated using commercial TiO2. In order to evaluate the photovoltaic performance of DSSCs, photocurrent density to photovoltage (J-V) characteristic and electrochemical impedance spectroscopy (EIS) measurements were carried out. The DSSC fabricated using combustion synthesized and commercial TiO2 exhibited a power conversion efficiency of 6.11% and 6.62%, respectively. Combustion synthesized TiO2 which displayed similar efficiency to that of commercial material is least studied in the literature for solar cell applications.
Keywords: Combustion synthesis; Dye sensitized solar cell; TiO2